ANALISIS KANDUNGAN FORMALIN PADA IKAN ASIN YANG BEREDAR DI PASAR CIAWITALI GARUT DENGAN METODE ACIDI ALKALIMETRI - Dani Sujana (Akademi Kesehatan John Paul II Pekanbaru, 2020)
Formalin is a formaldehyde compound which contains approximately 30-40% in water. This study aims to determine the level of formalin content in salted fish sold in the Ciawitali market, Garut, West Java qualitatively with KMnO4 reagent and quantitatively using the acidia alkalimetry method. The results of the study using 14 random samples proved that there were 10 types of salted fish with different levels of formalin, ranging from 4.44% to 5.40%, while 4 types of salted fish negatively contained formalin.